Modeling of magnetic vestibular stimulation experienced during high-field clinical MRI - Ismael Arán-Tapia; Vicente Pérez-Muñuzuri; Alberto P. Muñuzuri; Andrés Soto-Varela; Jorge Otero-Millan; Dale C. Roberts; Bryan K. Ward (Communications Medicine)
Abstract Background High-field magnetic resonance imaging (MRI) is a powerful diagnostic tool but can induce unintended physiological effects, such as nystagmus and dizziness, potentially compromising the comfort and safety of individuals undergoing imaging. These effects likely result from the Lorentz force, which arises from the interaction between the MRI's static magnetic field and electrical currents in the inner ear. Yet, the Lorentz force hypothesis fails to explain observed eye movement patterns in healthy adults fully. This study explores these effects and tests whether the Lorentz force hypothesis adequately explains magnetic vestibular stimulation. Methods We developed a mathematical model integrating computational fluid dynamics, fluid-structure interaction solvers, and magnetohydrodynamic equations to simulate the biomechanical response of the cristae ampullares. Using high-resolution micro-CT data of the human membranous labyrinth, we ensured anatomical accuracy. Experimental validation involved measuring horizontal, vertical, and torsional slow-phase eye movements in healthy subjects exposed to varying magnetic field intensities and head positions. Results Our model accurately replicates observed nystagmus patterns, predicting slow-phase eye velocities that match experimental data. Results indicate that Lorentz force-induced stimulation of individual cupulae explains variability in eye movements across different magnetic field intensities and head orientations. Conclusions This study empirically supports the Lorentz force hypothesis as a valid explanation for magnetic vestibular stimulation, offering new insights into the effects of high-field MRI on the vestibular system. These findings provide a foundation for future research and improved clinical practices.